New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
This Selected Issues paper discusses the issues related to reforms and growth in New Zealand. The paper analyzes the record on growth and productivity outcomes in a comparative perspective. The study provides a brief history of the industrial relations in New Zealand leading up the passage of the employment contracts act. The paper assesses the monetary policy framework, central bank decision-making processes, and also reviews the possible extensions to full funding of the country's future superannuation expenditures.